Jesus as a Wounded Woman: A Postcolonial Feminist Trauma Reading of Emanuel Garibay's Emmaus - Donald Steven Keryapi; Rosnita Temba Kagu (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This article uses Emanuel Garibay's painting